EFFECT OF STECKLING SIZE ON SEED YIELD AND QUALITY OF RADISH VAR. JAPANESE WHITE UNDER TEMPERATE CLIMATE - Kumar, P.R.; IDNANI, LK.; YADAV, SHIV K.; LAL, S. K.; Singh, RAMANJEET (Annals of Agricultural Research, 2014)
An investigation was carried out to study the effect of steckling size on vegetative growth, flowering date, seed yield, 1000-seed weight and germinability. It was observed that steckling of 1/3rd of the root size took the longest time to 50% flowering and 100% flowering and the whole root took the shortest time to 50% flowering and 100% flowering whereas the steckling of 2/3rds of root size showed intermediate effect for days to flowering. Whole root also resulted in highest yield as compared to root and 2/3rds root. Seed quality attributes viz., 1000 seed weight and seed germination Â were also found to be affected significantly by the size of stecklings in both years In year 2001-02, the germination increased singnificantly in 2/3rds and full root over the control, however, the increase in germination was at par in latter treatments. In the 2nd year, the germination significantly increased with increase in steckling size. Larger steckling can be recommended for higher seed yields of radish under temperate climate.